Learning from Failure: A Review of Peter Schuck's Why Government Fails So Often: And How It Can Do Better - Levy, David M.; Peart, Sandra J. (Journal of Economic Literature, 2015)
Peter Schuck catalogs an overwhelming list of US government failures. He points to both structural problems (culture and institutions) and incentives. Despairing of cultural change, Schuck focuses on incentives. He relies on Charles Wolf 's theory of nonmarket failures in which “internalities” replace the heavily-studied market failure from externalities (Wolf 1979). Internalities are evidence of a discord between the public goals by which a program is defended and the private goals of its administrators. What might economists contribute? We suggest that economists have neglected internalities because they take group goals as exogenously determined and we defend an alternative tradition in which group goals are endogenously determined.(JEL A11, D72, D82)